Answer:
If the sequence is the following:
c(n) = -7+6 (n-1)
c(1) = -7 + 6(1-1) = -7 + 6(0) = -7+0 = -7
c(2) = -7 + 6(2-1) = -7 + 6(1) = -7 +6 = -1
c(3) = -7 + 6(3-1) = -7 + 6(2) = -7 + 12 = 5
c(4) = -7 + 6(4-1) = -7 + 6(3) = -7 + 18 = 11
Explanation:
If the sequence is the following:
c(n) = -7+6 (n-1)
And we want to find the first four terms, so w ejust need to replace the values for n =1,2,3,4 and see what we got:
c(1) = -7 + 6(1-1) = -7 + 6(0) = -7+0 = -7
c(2) = -7 + 6(2-1) = -7 + 6(1) = -7 +6 = -1
c(3) = -7 + 6(3-1) = -7 + 6(2) = -7 + 12 = 5
c(4) = -7 + 6(4-1) = -7 + 6(3) = -7 + 18 = 11